Metaverse Crypto Dlt - .N, Anand; A, Aruna; AK, Dhanush; MP, Gowtham .; .S, Janunadevi; R, Kapilan. (Journal of Neonatal Surgery, 2025)
The revolutionary decentralized platform that brings together virtual reality, cryptocurrency, and Distributed Ledger Technology (DLT) is the Metaverse Crypto DLT project. Users can immerse themselves in a shared, interacti’e virtual world where they can create, experience, and monetize unique digital assets and experiences thanks to this innovative ecosystem. The platform makes sure that transactions take place in a safe, transparent, and tamper-proof environment by utilizing the power of DLT. This builds trust and confidence among users. A custom cryptocurrency is at the center of the platform. It was made to make transactions easier and to encourage ecosystem participation. Users can buy, sell, and trade digital assets like experiences, virtual real estate, and artifacts in a secure and efficient manner with this native cryptocurrency. Additionally, the platform’s DLT architecture guarantees the integrity and provenance of digital assets by recording all transactions on a public ledger. A number of ground-breaking features are included in the Metaverse Crypto DLT project, such as a decentralized governance model that enables users to participate in decision-making processes and shape the platform’s future. In addition, the platform’s AI-driven content creation tools let users create and personalize their own digital experiences, including interactive games, simulations, and virtual environments. The Metaverse Crypto DLT project has far-reaching implications for entertainment, education, healthcare, and commerce due to the convergence of cutting-edge technologies. This platform has the potential to open up new revenue streams, develop novel business models, and rethink the boundaries of human interaction and creativity by democratizing access to digital assets and virtual worlds